2018
DOI: 10.1590/1414-431x20187310
|View full text |Cite
|
Sign up to set email alerts
|

Familial history of hypertension-induced impairment on heart rate variability was not observed in strength-trained subjects

Abstract: Family history of hypertension is an important predictive factor for hypertension and is associated with hemodynamic and autonomic abnormalities. Previous studies reported that strength training might reduce arterial blood pressure (AP), as well as improve heart rate variability (HRV). However, the benefits of strength training in the offspring of hypertensive parents have not been fully evaluated. Here, we analyzed the impact of strength training on hemodynamics and autonomic parameters in offspring of hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Recent study showed that sedentary offspring of hypertensives, in contrast with the strength-trained group, presented impairment of total variance of RR interval, as well as an increase in cardiac sympathovagal balance (25).…”
Section: Resultsmentioning
confidence: 99%
“…Recent study showed that sedentary offspring of hypertensives, in contrast with the strength-trained group, presented impairment of total variance of RR interval, as well as an increase in cardiac sympathovagal balance (25).…”
Section: Resultsmentioning
confidence: 99%
“…The International Physical Activity Questionnaire (IPAQ, version 6) was administered to all subjects in order to establish the level of physical activity as previously described 17 .…”
Section: Methodsmentioning
confidence: 99%
“…During the period of the study evaluation, subjects were instructed to avoid alcohol and caffeinated beverages for the preceding 12 h and were invited to come to the laboratory between 08.30 and 12.30 as described elsewhere 17 . On arrival, the subjects underwent routine clinical examination and anthropometric measurements, such as weight, height, and BMI, were obtained while lean mass and percentage body fat were evaluated by bioimpedance (Biodynamics 450).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations